Barriers to replacing single-use packaging with circular reuse business models: a UK and Vietnamese context - Cullen, Elizabeth; Yang, Miying; Sule, May N. (Elsevier, 2026)
Replacing single use plastic packaging with repeatedly refilled reusable containers is a ‘refill on the go’ business model that can contribute to circular economy objectives. Despite potential to enable sustainable consumption, reuse business models frequently fail. Research into barriers to widespread adoption is scant, with blame for poor uptake frequently attributed to consumer behaviour. Knowledge of country specific barriers is also low, thus delaying political engagement with reuse solutions. To address these gaps, we adopted mixed methods combining 11 semi-structured interviews with an online consumer survey (n=326) in Vietnam and the UK. By triangulating multi-stakeholder views, we identified eight interrelated internal (consumer- and business-related) barriers and external (policy- and regulatory- related) barriers to the adoption of ‘refill on the go’ business models. Barriers overlapped, and some were country specific: low profit margins, knowledge and product provenance were identified by Vietnamese refill sector stakeholders, whereas hygiene, allergies and customer engagement were barriers in the UK. We observed consumer willingness to engage with refill business models struggling to gain and maintain footing in the competitive retail sector. We argue that effective adoption and scaling require top-down interventions, starting with policy and education, supported by context-specific strategies. Our findings suggest that barriers may be more easily addressed in Vietnam than the UK owing to a more central state role, flexible sector and lower recycling uptake. This research alerts policymakers to the challenges of a circular business model that is unlikely to grow to scale without bold, urgent and regionally appropriate policy support.
Keywords: 41 Environmental Sciences; 40 Engineering; 8.1 Organisation and delivery of services; Generic health relevance; 12 Responsible Consumption and Production; 4011 Environmental engineering; 4104 Environmental management; Refill; Reuse; Vietnam; UK; Circular economy; Circular business model